Neuroleadership in Twenty-First-Century Education: A Systematic Review - Yuli T. Revilla-Briceño; Segundo E. Cieza-Mostacero; Jenry A. Hidalgo-Lama (Emerging Science Journal, 2025)
In today’s volatile and interconnected world, characterized by economic uncertainty, competitiveness, and constant demands for transformation, organizations are challenged to adapt effectively to new requirements. This study presents a systematic review of 31 peer-reviewed articles published between 2014 and 2025 that examine neuroleadership in both managerial and educational contexts. The review offers a comprehensive framework that links leadership challenges with organizational strategies designed to transform work and academic practices. Findings highlight the benefits of neuroleadership in enhancing emotional well-being, engagement, decision-making, organizational resilience, and the development of both cognitive and emotional skills, as well as sustainability. The evidence further underscores the need to cultivate leaders who are capable of managing teams with empathy and strategic insight, thereby fostering more adaptive and human-centered workplace cultures. Overall, neuroleadership emerges as an innovative and essential paradigm for twenty-first-century leadership, rooted in cognitive processes and focused on the holistic development of human talent. Its successful implementation requires strategic vision, specialized training, and organizational commitment to address emerging challenges.